UPAYA HUKUM TERHADAP PENOLAKAN KLAIM ASURANSI JIWA OLEH PT PRUDENTIAL LIFE ASSURANCE CABANG GATSU - Devi Natasia, Komang Ayu; Agung, I Gst. Nyoman; Sukranatha, A.A. Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
One purpose of a life insurance contract, in addition to providing protection for the insured can also be used as an investment. If you experience any of the insured events as listed in the policy, the insured is entitled to make a claim. But not all claims can be accepted by the insurance company, so as to solve these problems required remedy. Keywords: Agreement, Life Insurance, Claims, Remedies
Keywords: Perjanjian, Asuransi Jiwa, Klaim, Upaya Hukum